Anticipatory and Anticipated Emotions in Regular and Non-regular Exercisers – A Qualitative Study - Feil, Katharina; Weyland, Susanne; Fritsch, Julian; Wäsche, Hagen; Jekauc, Darko (Frontiers in Psychology, 2022)
Future-oriented emotions could influence our decisions in everyday life and help understand why some individuals are physically active whilst others are not. Current literature distinguishes between two future-oriented emotion constructs: anticipatory and anticipated emotions. While anticipatory emotions are currently experienced emotions about a future event, anticipated emotions refer to the emotions that a person is expected to experience when confronted with a future event. The main aims of the present study were (1) to identify and describe (a) categories of anticipatory emotions experienced before exercise, and (b) categories of anticipated emotions expected to be experienced during and after exercise, and (2) to develop a theoretical model of anticipated emotion categories. Sixteen participants (Mage = 26.03, SD = 6.66) were recruited for semi-structured interviews, and their statements were analyzed using principles of the Grounded Theory. In total, 13 different anticipatory and anticipated emotion categories were identified, such as enjoyment, anxiety, pride, self-anger, and relief. Anticipatory emotions seem to reflect the current affective valence of exercising and may be influenced by daily factors. With regards to anticipated emotions, the results show that regular exercisers anticipated also negative emotions such as anxiety, disappointment, and self-anger, and non-regular exercisers also anticipated positive emotions such as enjoyment, pride, and satisfaction. Therefore, future research should not only focus on the valence of future-oriented emotions, but should investigate the possible impact of specific anticipated emotions on exercise behavior. In addition, a theoretical model of anticipated emotion categories in exercise behavior derived from the interviews. The model outlines different categories of anticipated emotions based on appraisal processes. In conclusion, we assume that this developmental process of anticipated emotions may be embedded in a broader, cyclical process within the context of exercising.